Electrolysis of metal oxides in MgCl2 based molten salts with an inert graphite anode - Yuan, Yating; Li, Wei; Chen, Hualin; Wang, Zhiyong; Jin, Xianbo; Chen, George Z. (Royal Society of Chemistry, 2016)
Electrolysis of solid metal oxides has been demonstrated in MgCl2–NaCl–KCl melt at 700 °C taking the electrolysis of Ta2O5 as an example. Both the cathodic and anodic processes have been investigated using cyclic voltammetry, and potentiostatic and constant voltage electrolysis, with the cathodic products analysed by XRD and SEM and the anodic products by GC. Fast electrolysis of Ta2O5 against a graphite anode has been realized at a cell voltage of 2 V, or a total overpotential of about 400 mV. The energy consumption was about 1 kW h kgTa−1 with a nearly 100% Ta recovery. The cathodic product was nanometer Ta powder with sizes of about 50 nm. The main anodic product was Cl2 gas, together with about 1 mol% O2 gas and trace amounts of CO. The graphite anode was found to be an excellent inert anode. These results promise an environmentally-friendly and energy efficient method for metal extraction by electrolysis of metal oxides in MgCl2 based molten salts.